A quality systems study of Meden Arellano Enterprises - Caisip, Jay H.; Lachica, Edlyn S.; Moncada, Marchae Gizette B. (Diliman, Quezon City College of Engineering, 1996)
A quality systems study was conducted on Meden Arellano Enterprises, a medium-scale garments manufacturing company, from July to August 1995. Statistical quality methods, quality audits, and total quality techniques were applied, and the following quality-related problem areas were identified: poor level of quality awareness lack of use of statistic al tools in inspection lack of material inspection procedures To address these problem areas, the following recommendations were subsequently formulated: introduction of Total Quality Management on a company wide basis, the use of SPC in the inspection process intensive consultations with these textile industry organizations: Philippine Textile Research Institute and the Garments and Textiles Export Board
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Meden Arellano Enterprises; Clothing trade; Quality control